Day 1 Mon, May 04, 2020 2020
DOI: 10.4043/30800-ms
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm Shift in Downhole Sand Control; The First Installation of Shape Memory Polymer as an Alternative to Gravel Packing at BS Field, Offshore Malaysia

Abstract: Controlling sand has been one of the most difficult challenges in oil production in Upstream Malaysia operations. Conventionally, Cased Hole Gravel Packs (CHGP) or Open Hole Gravel Packs (OHGP) are installed to prevent sand from being produced with the oil to the surface facilities. However, both methods require massive operations and high cost which impact the overall economics of the project. This paper summarizes the technology evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thermally actuated SMPs are the most commonly used materials, for example, intelligent plugging drilling fluids [ 9 ], self-expanding cement [ 10 , 11 ], intelligent sand control technology [ 12 , 13 ], etc. Field tests and laboratory studies have demonstrated that technologies involving SMPs have significantly improved oil recovery rates [ 14 ]. Recently, a packer made of thermo-responsive shape memory polymers with a smaller size has been proposed as a potential seal component [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thermally actuated SMPs are the most commonly used materials, for example, intelligent plugging drilling fluids [ 9 ], self-expanding cement [ 10 , 11 ], intelligent sand control technology [ 12 , 13 ], etc. Field tests and laboratory studies have demonstrated that technologies involving SMPs have significantly improved oil recovery rates [ 14 ]. Recently, a packer made of thermo-responsive shape memory polymers with a smaller size has been proposed as a potential seal component [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted on similar well for sandstone formations strengthen by open hole gravel pack (OHGP) have average productivity increment up to 40% for several gas wells in Cambay Bay the coast of India [7] Based on calculation of gas well deliverability with Inflow Performance Relationship -IPR [8], pre-matrix acidizing productivity of deepwater GWK-8 is below expectation. The application of Shape Memory Polymer (SMP) sand control at wellbore is required to increase the strength of wellbore for the purpose of achieve an optimal gas rate [9] which has a pore throat diameter 50 microns that prevent any sand break out. Wellbore with Shape Memory Polymer (SMP) sand control system is going to be normalized by matrix acidizing to dissolved wellbore impurities and damage to achieve optimum skin (s), porosity (Φ), permeability (k), and deliverability (Q).…”
Section: Introductionmentioning
confidence: 99%
“…Matrix acidizing at sandstone formation strengthen by Shape Memory Polymer (SMP) the new technology of sand control system will improve production deliverability in significant numbers [4,5,9]. The improvement of production deliverability proven by accurate well-testing; post-matrix acidizing skin (s), permeability (k), and Inflow Performance Relationship (IPR) are improved significantly.…”
Section: Introductionmentioning
confidence: 99%